APLIKASI PROGRAM MULTIMEDIA UNTUK ANAK TK MULTIMEDIA APPLICATIONS PROGRAM FOR CHILDREN KINDERGARTEN (Information Technology and Telematics, 2012)
Application with multimedia systems are expected children can learn quickly and easily understood. This study aids program design using Macromedia Flash MX. This application is designed to help children, especially kindergarten children in the learning process in recognizing numbers, letters, shapes, colors, animals and fruits. Development methodology used is a multimedia development methodology. Intent and purpose of this program so that they could be interested to learn and play as if it were not learning the program was created consisting of text, sound and image with some motion pictures. This multimedia program on the application there are also exercises in addition to learning but also be able to implement it by answering questions that have been provided.   keywords : Applications, Children kindergarten, Multimedia, Macromedia Flash MX